On studying money from the top down: A comment on "Inflation - Pragmatics of money and inflationary sensoria" by Federico Neiburg - Guadalupe Moreno (economic sociology. perspectives and conversations, 2023)
In "Inflation - Pragmatics of money and inflationary sensoria" (this issue), Federico Neiburg continues to expand the sociological reflection on money's uses in the unstable landscapes of the financial periphery. As he shows, in these landscapes, frequent currency crises and inflationary processes disrupt established monetary routines and encourage the emergence of creative solutions and new habits that help to combat price increases.
Keywords: 300